Pengembangan Modul Menulis Puisi Berbasis Pendekatan Kontekstual untuk Meningkatkan Hasil Belajar - Suhadaningsih, Khori; Nugrahani, Farida; Widayati, Mukti (Jurnal Pendidikan Madrasah, 2024)
This study aims to describe the module of Poetry Writing Based on Contextual Approaches to improve learning outcomes. This study used the R&D method of Borg and Gall. The subject of the study was a student of grade VIII D MTs Negeri 3 Gunungkidul. The results showed (1) Product characteristics of the Contextual Approach-Based Poetry Writing module as follows: a) in the form of a printed module of Contextual Approach-Based Poetry Writing; b) the material presented is associated with things around life, so that students more easily understand the material; c) module preparation refers to the contextual learning flow; d) the module contains material for writing poetry based on a contextual approach contained in contextual steps; e) Modules can be used in classroom learning and self-study for students at home. 2) The feasibility of the Contextual Approach Based Poetry Writing module based on the assessment of experts, practitioners, teacher, and student responses provides excellent categories and deserves to be used. 3) the product is effective in increasing knowledge, (N-gain score 0.6533), attitude (6%), and skills (9%).